Réponses

  • Utilisateur Brainly
2014-04-28T12:17:52+02:00
Exo 1 :

A² = (V5+3)² = 5+6V5+9 = 6V5+14
B² = (V5-3)² = 5-6V5+9  = -6V5+14
AB =(V5+3)(V5-3) = (a-b)(a+b) =a²-b² = 5-9 = -4
(A+b)² = [(V5+3)+(V5-3)]²
           = (V5+3+V5-3)²
           = (2V5)²
           = 20

2)  \frac{V5+3}{V5-3} + \frac{V5-3}{V5+3} =
   [(V5+3)(V5+3)+(V5-3)(V5-3)]/((V5-3)(V5+3)+(V5+3)(v5-3) =
   5+3v5+3V5+5-3V5-3V5+9)/-4 =
   19/-4 = -19/4

eox 2 :

1) x²

2) (2+v2)² = 4+4V2+2 = 4V2+6

3) [(x-0,5)*4]/2 = 4x-2)/2 = 2x-1

4) (2x-1) pour x =(V2+2)
   2(V2+2)-1 = 2V2+4-1 = 2V2+3

5) 4V2+1+2V2+3 = 6V2+4 = 2(3v2+2)